ARID1A, a SWI/SNF subunit, is critical to acinar cell homeostasis and regeneration and is a barrier to transformation and epithelial-mesenchymal transition in the pancreas. Issue 7 (18th September 2018) - Wang, Wenjia; Friedland, Scott C; Guo, Bing; O'Dell, Michael R; Alexander, William B; Whitney-Miller, Christa L; Agostini-Vulaj, Diana; Huber, Aaron R; Myers, Jason R; Ashton, John M; Dunne, Richard F; Steiner, Laurie A; et al.
Abstract : Objective: Here, we evaluate the contribution of AT-rich interaction domain-containing protein 1A ( ARID1A ), the most frequently mutated member of the SWItch/sucrose non-fermentable (SWI/SNF) complex, in pancreatic homeostasis and pancreatic ductal adenocarcinoma (PDAC) pathogenesis using mouse models. Design: Mice with a targeted deletion of Arid1a in the pancreas by itself and in the context of two common genetic alterations in PDAC, Kras and p53, were followed longitudinally. Pancreases were examined and analysed for proliferation, response to injury and tumourigenesis. Cancer cell lines derived from these models were analysed for clonogenic, migratory, invasive and transcriptomic changes. Results: Arid1a deletion in the pancreas results in progressive acinar-to-ductal metaplasia (ADM), loss of acinar mass, diminished acinar regeneration in response to injury and ductal cell expansion. Mutant Kras cooperates with homozygous deletion of Arid1a, leading to intraductal papillary mucinous neoplasm (IPMN). Arid1a loss in the context of mutant Kras and p53 leads to shorter tumour latency, with the resulting tumours being poorly differentiated. Cancer cell lines derived from Arid1a -mutant tumours are more mesenchymal, migratory, invasive and capable of anchorage-independent growth; gene expression analysis showed activation of epithelial-mesenchymal transition (EMT) and stem cell identity pathways that are partially dependent on Arid1a loss for dysregulation. Conclusions: ARID1A plays a key role in pancreatic acinar homeostasis and response to injury. Furthermore, ARID1A restrains oncogenic KRAS-driven formation of premalignant proliferative IPMN. Arid1a -deficient PDACs are poorly differentiated and have mesenchymal features conferring migratory/invasive and stem-like properties.